Juxta-articular extraskeletal myxoid chondrosarcoma mistaken for a benign cyst presenting with multiple lung metastases - Dmitriy Starostin, MBChB, FRCR; Ibrahim Azam, MD, MRCS, FRCR; Michael Paddock, MSc, MBBS, FRCR; Malee S. Fernando, MD, FRCPath; Scott Evans MBChB, MRCS, FRCS; Nikhil Kotnis, MBChB, FRCR (Radiology Case Reports, 2024)
Extraskeletal myxoid chondrosarcoma (EMC) is a malignant cartilage neoplasm usually encountered in the proximal extremities. We report the case of a 58-year-old male who presented initially with a 3-month history of cough. Initial staging demonstrated a right upper lobe mass with bilateral pulmonary nodules and moderate tracer uptake in the right lung mass and right groin on positron emission tomography imaging. Endobronchial ultrasound biopsy confirmed a histological diagnosis of EMC for which the patient underwent right upper lobe wedge resection. Pelvic MRI revealed a peripherally enhancing juxta-articular lesion within the region of the right obturator externus bursa, which was thought initially to represent either a ganglion or paralabral cyst. However, ultrasound-guided biopsy yielded identical histology to the resected lung mass leading to the diagnosis of primary EMC in the right groin with pulmonary metastases. The patient underwent surgical excision of the right groin mass with no local recurrence on the surveillance computed tomography at 5, 12, and 18 months but eventual disease recurrence in the right groin and further progression of the pulmonary metastases at 29 months. We emphasize that the contrast enhancement pattern of EMC can mimic a benign cystic lesion, in particular, when in a juxta-articular location, which has the potential to mislead radiologists and delay diagnosis and definitive treatment.